PENGARUH ACCELERATED LEARNING CYCLE TERHADAP KEMAMPUAN KONEKSI MATEMATIS SISWA SEKOLAH DASAR - Muhammad Fendrik; Siti Quratul Ain; Eva Astuti Mulyani (Tunjuk Ajar: Jurnal Penelitian Ilmu Pendidikan, 2018)
This research in the background by the importance of good mathematical connection ability must be mastered by elementary students as one of the goals of learning mathematics. The purpose of this study, namely: 1) describe and compare students who received learning Accelerated Learning Cycle and Conventional Learning to the ability of mathematical connections; 2) describe and compare the ability of mathematical connections and students' early mathematical abilities. This research is quasi-experimental research with experimental design in the form of group comparison. In this research plan, the sample used consisted of two groups, wherein each group applied different learning. The first group (experimental group) received learning Accelerated Learning Cycle, the second group (control group) applied conventional learning. The research location is in SD Negeri 136 Pekanbaru which is a medium category school. Categories are becoming the researcher's choice because the schools in this category are mostly schools in Pekanbaru City. Based on the results of data processing, analysis, and discussion that has been presented, obtained the conclusion, namely: 1) improvement of mathematical connection ability of students who obtained learning with Accelerated Learning Cycle better than students who received conventional learning. Where the average mathematical connection ability of students who get Accelerated Learning Cycle (experimental class) is 22.78, while the average mathematical connection ability of students who obtain conventional learning (control class) is 17.03; 2) There is no significant difference in mathematical connection ability of students who obtained learning with Accelerated Learning Cycle in terms of students' mathematical ability. The significance value of the equivalence test of mathematical connection data of control class students and experiment class, this is indicated by the significance value of both categories is more than 0.025. Whereas in the initial ability of low category, the significance value less than 0.025, so the null hypothesis is rejected, which means the mathematical connection ability of the experiment class students is better than the control class.